2023
DOI: 10.3390/ijms24129942
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E Analog Trolox Attenuates MPTP-Induced Parkinson’s Disease in Mice, Mitigating Oxidative Stress, Neuroinflammation, and Motor Impairment

Abstract: Trolox is a potent antioxidant and a water-soluble analog of vitamin E. It has been used in scientific studies to examine oxidative stress and its impact on biological systems. Trolox has been shown to have a neuroprotective effect against ischemia and IL-1β-mediated neurodegeneration. In this study, we investigated the potential protective mechanisms of Trolox against a 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced Parkinson’s disease mouse model. Western blotting, immunofluorescence staining, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…In this study, Matsura, (2019) observed that tocotrienol exerts its cytoprotection through a novel mechanism which includes membrane ERβ/PI3K/Akt signaling via caveola formation as well as its antioxidant activity. An analogue of vitamin E, Trolox was recently reported by Atiq et al (2023) to inhibit activated astrocytes (GFAP) and microglia (Iba-1), also reduces phosphorylated nuclear factor-κB, (p-NF-κB) and tumor necrosis factor-alpha (TNF-α) in the PD mouse brain. Just recently, vitamin E administration was reported to offer neuroprotective function on manganese-induced neurodegeneration in the nigrostriatal system.…”
Section: Role Of Nutritional-derived Antioxidants and Their Mechanism...mentioning
confidence: 99%
“…In this study, Matsura, (2019) observed that tocotrienol exerts its cytoprotection through a novel mechanism which includes membrane ERβ/PI3K/Akt signaling via caveola formation as well as its antioxidant activity. An analogue of vitamin E, Trolox was recently reported by Atiq et al (2023) to inhibit activated astrocytes (GFAP) and microglia (Iba-1), also reduces phosphorylated nuclear factor-κB, (p-NF-κB) and tumor necrosis factor-alpha (TNF-α) in the PD mouse brain. Just recently, vitamin E administration was reported to offer neuroprotective function on manganese-induced neurodegeneration in the nigrostriatal system.…”
Section: Role Of Nutritional-derived Antioxidants and Their Mechanism...mentioning
confidence: 99%
“…Aβ 25-35 plays a significant catalytic role in this process ( Smith and Klimov, 2019 ). In patients with AD and PDD, there is often an increase in lipid hydroperoxide (L-OOH) and malondialdehyde (MDA) activity, alongside decreased activity of antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT), and glutathione (GSH) ( Chen et al, 2022 ; Atiq et al, 2023 ). Moreover, the brain’s rich content of metal ions, such as iron, facilitates oxidative stress and DNA damage through the Haber-Weiss reaction ( Suma et al, 2020 ), and promotes the aggregation of α-synuclein, leading to the formation of Lewy bodies—a key pathological feature of PDD and Lewy body dementia ( Wakabayashi et al, 2007 ).…”
Section: Pharmacological Effects Of Saponin Compoundsmentioning
confidence: 99%
“…Vitamin E (α-tocopherol) is a lipid-soluble vitamin, enhancing immunity and reducing OS (Wang et al, 2023). Atiq A et al published an article regarding the impact of vitamin E using an experimental model of Parkinson's disease, reducing α-synuclein expression, increasing the expression of dopamine transporter in the substantia nigra and activating the nuclear factor erythroid-2-related factor 2 (Nrf2) pathways (Atiq et al, 2023).…”
Section: Vitamin Ementioning
confidence: 99%